An Analysis of Teacher’s Strategies in Teaching English Speaking: Descriptive qualitative study - Masruroh, Lailatul; Mazidah, Eva Nur (Universitas Terbuka, 2025)
Speaking in junior high school is one of the four English skills that students have to learn. The objective of this research is to find out the strategies used in teaching speaking skills to the eighth graders students at UPT SMP Negeri 32 Gresik. The problem of this research is what are teacher’s strategies used in teaching speaking skill of the eighth graders at UPT SMP Negeri 32 Gresik. The design of this research is descriptive-qualitative research. The population of this research is the English teacher for eighth graders at UPT SMP Negeri 32 Gresik. The sample for this research is the teacher who teaches eighth graders. The writer uses observation, interview, questionnaire, field notes, and documentation for collecting the data, and the results of the instruments were described in a descriptive way. The findings in research at UPT SMP Negeri 32 Gresik that English teachers use one learning strategy, namely the Teacher Center, there are many good responses from students to the strategies given by the English teacher. In addition, students also feel that they can receive speaking material well because the strategies provided by students are helped by the strategies implemented by the teacher to increase their confidence in speaking English. besides that, the teacher also uses media in the form of whiteboard, marker, and module